Polyoxometalate@MIL-101/MoS2: a composite material based on the MIL-101 platform with enhanced performances. (5th February 2019) - Liang, Dadong; Liang, Chen; Meng, Lingkun; Lou, Yue; Li, Chunguang; Shi, Zhan
Abstract : MIL-101 was used as a platform to integrate two functional materials for achieving enhanced dye adsorption and separation performances. Abstract : A composite was designed and synthesized based on MIL-101, MoS2, and an iron-substituted polyoxometalate. MoS2 and PW11 O39 Fe(H2 O) 4− (PW11 Fe) were introduced on the surface of MIL-101 and encapsulated in the cages of MIL-101, respectively. First, a facile microwave synthesis method was developed for synthesizing the composite MIL-101/MoS2 . Then, PW11 Fe clusters were diffused into the pores of MIL-101/MoS2 . The composite PW11 Fe@MIL-101/MoS2 could rapidly adsorb rhodamine B (RhB). An adsorption capacity of 378 mg g −1 was achieved in the first 5 min. Moreover, PW11 Fe@MIL-101/MoS2 could be potentially used for the separation of dyes. Its RhB adsorption capacity at equilibrium was about four times higher than that of MIL-101. In contrast, its methyl orange (MO) adsorption capacity was about three times lower than that of MIL-101.